Comparative analysis of CGUARD embolic prevention stent with Casper-RX and Wallstent for the treatment of carotid artery stenosis. (May 2020) - Abdullayev, N.; Maus, V.; Mpotsaris, A.; Henning, T.D.; Goertz, L.; Borggrefe, J.; Chang, D.H.; Onur, OA.; Liebig, T.; Schlamann, M.; Kabbasch, C.
Highlights: CGUARD stents is feasible and safe compared to one layer stents in symptomatic and asymptomatic patients. The rate of thromboembolic complications compares favorably with Wallstent for emergent, urgent and elective cases. No significant differences in the rate of acute in-stent occlusions among the 3 groups. No significant differences in the rate of postinterventional symptomatic intracerebral hemorrhage among the 3 groups. Abstract: Stent protected Angioplasty of extracranial carotid artery stenosis using the dual-layered CGUARD stent is a novel treatment option. In this study we evaluate the feasibility and the safety of the CGUARD in symptomatic and asymptomatic patients in comparison to Casper-RX and Wallstent. This is a multi-center study of consecutive patients treated with the CGUARD, Casper-RX and Wallstent at two German high volume neurovascular centers between April 2017 and May 2018. Patient characteristics, neuroimaging data and angiographic outcome were retrospectively analyzed. The primary end points of the study were acute occlusion of the carotid stent and symptomatic intracerebral hemorrhage (sICH). Carotid artery stenting was performed in 76 patients; of those 26 (34%) were treated with the CGUARD, 25 (33%) with Casper-RX, and 25 (33%) with Wallstent. In 58/76 (76%) cases carotid artery stenosis was symptomatic with a median baseline National Institutes of Health Stroke Scale of 4. Angioplasty and stenting as part of a mechanical thrombectomy for acute ischemic stroke was performed in 25/76 (33%) patients. Baseline patient characteristics were similar between the treatment groups, except for a higher portion of scheduled cases in the Casper-RX group. There were no significant differences in the rate of acute in stent occlusions (CGUARD, 2/26 (8%); Casper-RX, 1/25(4%); Wallstent, 1/25 (4%)) and postinterventional sICH (1/26 (4%), 0/25(0%), 0/25 (0%)). Clinical outcome at discharge did not differ between groups. Treatment of carotid artery stenosis using CGUARD is feasible with a good safety profile comparable to that of Casper-RX and Wallstent.